2022
DOI: 10.1155/2022/7424748
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fasting Plasma Glucose Level on Admission of COVID-19 Patients: A Retrospective Study

Abstract: Background. The coronavirus disease 2019 (COVID-19) is a serious global health threat and has spread dramatically worldwide. Prolonged viral shedding is associated with a more severe disease course and inflammatory reaction. Blood glucose levels were significantly associated with an increased hazard ratio (HR) for poor outcomes in COVID-19 patients. Objective. Previous studies focused primarily on the relationship between blood glucose and mortality or severe outcomes, but there were few research studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The glucose level correlated with the poor outcome and prolonged SARS-CoV-2 shedding in Delta variant-infected patients. [19][20][21][22] Patients with lower uric acid levels were more likely to have severe symptoms. 23,24 It was speculated that the cellular and humoral immunity was impaired and the level of neutralizing antibodies reduced with age.…”
Section: Discussionmentioning
confidence: 99%
“…The glucose level correlated with the poor outcome and prolonged SARS-CoV-2 shedding in Delta variant-infected patients. [19][20][21][22] Patients with lower uric acid levels were more likely to have severe symptoms. 23,24 It was speculated that the cellular and humoral immunity was impaired and the level of neutralizing antibodies reduced with age.…”
Section: Discussionmentioning
confidence: 99%
“…It is very well known that the severity of COVID-19 infections is strongly influenced by comorbidities such as T2DM or cardiovascular disease that might lead to hospitalization during acute infections [ [1] , [2] , [3] ]. Interestingly, one retrospective study with 99 clinical COVID-19 patients found a relationship between fasting glucose levels and Sars-Cov2 duration that leads to the assumption that increased FPG levels are associated with a longer duration of SARS-CoV-2 RNA positivity in patients [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that glucose at admission is an independent risk factor for the poor prognosis of COVID-19 during the Delta variant wave [ 15 , 16 , 20 ]. Moreover, high glucose at admission is an independent predictor for prolonged SARS-CoV-2 shedding, irrespective of a history of diabetes [ 17 ]. Similar results were obtained in the present study during the Omicron variant wave.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, blood glucose predicted the mortality of coronavirus disease 2019 (COVID-19), even in patients without a history of diabetes [ 14 16 ]. High fasting plasma glucose level (≥ 6.1 mmol/L) at admission is an independent predictor for prolonged SARS-CoV-2 shedding [ 17 ]. Individuals with hyperglycemia had lower spike IgG titer than those with normoglycemia after two doses of the BNT162b2 vaccine, indicating that hyperglycemia is associated with a poor humoral immune response [ 18 ].…”
Section: Introductionmentioning
confidence: 99%